SIDANG PEMERIKSAAN SETEMPAT PADA PERADILAN HUBUNGAN INDUSTRIAL DALAM PELAKSANAAN ASAS PERADILAN CEPAT TEPAT ADIL DAN MURAH - Holyness Singadimeja; Sherly Ayuna Puteri (Departemen Hukum Perdata, 2018)
Basically, the procedural law of industrial relations court is quite similar to civil procedure apply in ordinary court. Article 57 of Law No. 2 of 2004 states that the procedural law apply in industrial relations court is civil procedure apply in ordinary court, unless particularly provided in Law No. 2 of 2004. It means that Law No. 2 of 2004 is lex specialis of HIR, RBg, or Rv. Site examination often held in civil proceeding to obtain certain evidence and make clear the case. Unfortunately, in industrial relations case, site examination may lead to obstacles for the judges and the parties, mostly for the employees, since the time limit to solve the case and the costs that should be paid by the parties.